Analytical and stochastic dependability model of cyber and cloud assets for SCADA system of the critical infrastructure - Ivanchenko, O. V. (Systems and Technologies, 2020)
Methodological provisions pertaining to necessary a dependability assurance of supervaisory control and data acquisition systems (SCADA) for critical infrastructures is based on analysis of contemporary development trend and operational usage of these systems. At the same time, an increased cyber threats level of the SCADA systems is prooved that developers and service personnel should improve bandwidth, disaster recovery and backup procedures of these systems. The issue can be eliminated by them based on the use of additional cloud systems and technologies. In the proposed paper, usage of a comprehensive approach in order to solve concerns relating to availability, safety of the cyber and cloud assets for SCADA of critical infrastructures is considered as one of the most important scientific task. Which is why the proposed analytical and stochastic dependability models are basis for a developing assessment procedure for SCADA of the critical infastructures, which can be implemented by researchers according to a deliberate malicious impact scenario on assets of SCADA for ritical infrastructures. It means that before begin to SCADA system developers and researchers will perform quite deep analysis based on a scientific study. Since how to determine dependability assessment for the SCADA system is an important issue that to be studied. Therefore, developers, service personnel and scientists should work together in order to create effective functioning protection system for cyber and cloud assets of SCADA. In addition, the service personnel should leverage especial cyber protection systems, devices and applications such as, firewalls, password cyberprotection subsystems etc. The author proposes to get more modeling numerical results based on the use of Markov Modeling Process. In fact, the modeling process was carried out in two parts. First part has included a building process of save and secure block diagram for cyber and cloud assets considering different types of deliberate malicious impacts. Second part was being devoted to the implementation Semi-Markov Modeling Process based on the use of overall architecture of the SCADA system.